The Association Between Oxidative Stress Alleviation via Sulforaphane-Induced Nrf2-HO-1/NQO-1 Signaling Pathway Activation and Chronic Renal Allograft Dysfunction Improvement - Daoyuan Lv; Qin Zhou; Yue Xia; Xu You; Zhihong Zhao; Yongqiang Li; Hequn Zou (Karger Publishers, 2018)
Background/Aims: Chronic renal allograft dysfunction (CRAD) is a leading cause of long-term renal allograft loss. Oxidative stress may account for the nonspecific interstitial fibrosis and tubular atrophy that occur in CRAD. An antioxidant intervention via Nrf2 signaling pathway activation might be a promising therapy for some kidney diseases. The present paper investigates whether there is an association between oxidative stress alleviation via sulforaphane-induced Nrf2-HO-1/NQO-1 signaling pathway activation and CRAD improvement. Methods: F344 rat kidneys were orthotopically transplanted into Lewis rat recipients to establish CRAD models. Sulforaphane was administered at 1.5 mg/kg intraperitoneally once daily. Renal function and 24-hour urinary protein were monitored for variations for 24 weeks after transplantation. After 24 weeks, renal histopathology was evaluated according to the Banff criteria after hematoxylin and eosin, Masson's trichrome and periodic acid-Schiff stainings. Additionally, intrarenal oxidative stress was assessed by the indicators malondialdehyde, 8-isoprostane, oxidized-low density lipoprotein and 8-hydroxy-2'-deoxyguanosine, as well as the activity levels of the antioxidant enzymes total superoxide dismutase, catalase, glutathione peroxidase, glutathione reductase and γ-glutamylcysteine synthetase. Nrf2, HO-1 and NQO-1 expression levels were determined via immunohistochemical and Western blot analyses. Results: The sulforaphane-induced Nrf2-HO-1/NQO-1 signaling pathway activation, as demonstrated by immunohistochemical and Western blot analyses, delayed the progression of serum creatinine and blood urea nitrogen, particularly lowering the 24-hour urinary protein levels of CRAD. The semi-quantified histopathological changes were also alleviated. Evidence of oxidative stress alleviation, as indicated by a concurrent decrease in the indicators and sustained levels of antioxidant enzymes activity, was found in the renal allografts after sulforaphane intervention. Conclusion: Oxidative stress alleviation caused by continuous sulforaphane-induced Nrf2-HO-1/NQO-1 signaling pathway activation is associated with functional and morphological improvements of CRAD.